2017
DOI: 10.1109/jlt.2016.2646921
|View full text |Cite
|
Sign up to set email alerts
|

Secure NFV Orchestration Over an SDN-Controlled Optical Network With Time-Shared Quantum Key Distribution Resources

Abstract: We demonstrate, for the first time, a secure optical network architecture that combines NFV orchestration and SDN control with quantum key distribution (QKD) technology. A novel time-shared QKD network design is presented as a cost-effective solution for practical networks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…The SDN controller is capable of realizing flexible and programmable global optical network management, which can be utilized as the effective implementation technique for control layer. Moreover, it has been demonstrated in the recent study on time-shared QKD resources in SDN-controlled optical networks [28].…”
Section: An Example Of Qkp For Secret Key Provisioning Between Node-amentioning
confidence: 94%
“…The SDN controller is capable of realizing flexible and programmable global optical network management, which can be utilized as the effective implementation technique for control layer. Moreover, it has been demonstrated in the recent study on time-shared QKD resources in SDN-controlled optical networks [28].…”
Section: An Example Of Qkp For Secret Key Provisioning Between Node-amentioning
confidence: 94%
“…These SDN functionalities are the key motivator for the integration of QKD in an SDN-enabled optical network, as shown in [15,16,17,18,19,20,21]. The current works have proved that the SDN integration is beneficial for the QKD networks for customized network configuration (e.g.…”
Section: Monitoring and Physical Layer Attack Mitigation In Sdn-contrmentioning
confidence: 97%
“…SDN holds a programmable and flexible centralized control manner to provide efficient and easy management for QKD networks. In [48], it was demonstrated that SDN can reduce costs in a QKD network for time-sharing of the available resources. In [49], SDN was introduced in a QKD network to provide real-time monitoring of quantum parameters, e.g., secret-key rate and quantum bit error rate.…”
Section: B Qkd Network Managementmentioning
confidence: 99%